Maars to calderas: end-members on a spectrum of explosive volcanic depressions - Palladino, Danilo M.; Valentine, Greg A.; Sottili, Gianluca; Taddeucci, Jacopo (Frontiers in Earth Science, 2015)
We discuss maar-diatremes and calderas as end-members on a spectrum of negative volcanic landforms (depressions) produced by explosive eruptions (note – we focus on calderas formed during explosive eruptions, recognizing that some caldera types are not related to such activity). The former are dominated by ejection of material during numerous discrete phreatomagmatic explosions, brecciation, and subsidence of diatreme fill, while the latter are dominated by subsidence over a partly evacuated magma chamber during sustained, magmatic volatile-driven discharge. Many examples share characteristics of both, including landforms that are identified as maars but preserve deposits from non-phreatomagmatic explosive activity, and ambiguous structures that appear to be coalesced maars but that also produced sustained explosive eruptions with likely magma reservoir subsidence. A convergence of research directions on issues related to magma-water interaction and shallow reservoir mechanics is an important avenue toward developing a unified picture of the maar-diatreme-caldera spectrum.